The cognitive character of proverbs and sayings about life in Shakarim’s poems - Amanbekkyzy Ж.; Syzdykova Г.О.; Khusainova Л.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article is devoted to the analysis of the cognitive function of proverbs and sayings in Shakarim Kudaiberdiuly’s poems. The study reveals their role in education, the transmission of cultural and moral values, as well as in the formation of a national worldview. The purpose of the scientific research is to analyze proverbs and sayings in Shakarim’s poems and determine their role in promoting values and strengthening national ideological foundations in human life. The article examines the structure and essence of paremiological units, their semantic features and their impact on the social and spiritual context. The scientific significance of the research lies in understanding the national character of proverbs and sayings in Shakarim’s poetry and forming a new approach to literary heritage from the point of view of linguistic cognition. And the practical significance is characterized by the definition of the possibility of using these proverbs in the modern education system. The methodology uses textual analysis, comparative historical method, case study and conceptual-logical approach. The results obtained confirm that Shakarim’s proverbs and sayings contribute to understanding the meaning of life, moral education, and the pursuit of knowledge and work. The practical significance of the work lies in its application in the field of linguistics, ethnolinguistics and youth education.